Effect of heat integration on dynamic of a palm-oil fractionation process - Ahmad, Arshad; Ling, Leong Yau (Faculty of Chemical and Natural Resources Engineering, UTM, 2001)
The needs to satisfy more stringent safety environmental regulations whilst maintaining the economic objective has drawn more attention towards multiple integration of process units leading to more challenging plantwide process control problem. In other to solve this growing problem, it is desirable to have rigorous models for realistic and large-scale processes. In this paper the development of dynamic models of a typical palm oil fractionation process using HYSYS. Plant simulation package is presented. Results illustrating the effect of recycle stream and heat integration to process control performance are also displayed and discussed.